The Dhikir and Prayer Therapy on Reducing Blood Pressure in Hypertension Patients: Systematic Literature Review - Sopiah, Popi; Nuryani, Reni; Sukaesih, Nunung Siti; Lindasari, Sri Wulan; Assyfa, Nurul (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Hypertension can lead to a variety of consequences, including death. Alternative therapies, such as Dhikr and prayer therapy, have emerged as a response to the negative effects of medications used to treat hypertension. The therapy of Dhikr and prayer worked by inhibiting sympathetic nerve dominance and activating parasympathetic nerves, resulting in a soothing effect. The goal of this paper was to conduct a literature search to determine the effectiveness of Dhikr therapy and prayer in lowering blood pressure in hypertension patients. The method involved investigating evidence published in electronic data from Google Scholar and Semantic Scholar. Using Publish or Perish, we searched for data from 2018 to 2023 using the terms "Dhikr therapy," "prayer therapy," and "hypertension." Using the Prisma Strategy flow chart, 11 relevant journals were eligible out of 352. The results showed that when a person recites Dhikr by focusing on words or sentences of prayer that are repeated with a regular rhythm, accompanied by an attitude of surrender to God, the individual will experience relaxation. This relaxed state could control the nervous system, which is responsible for regulating blood pressure in hypertensive patients leading to a decrease in blood pressure. Dhikr and prayer therapy are effective in reducing blood pressure in hypertensive patients. Recommendations suggest that Dhikr and prayer therapy can be applied as an alternative treatment for hypertension.